Effect of Dietary Supplementation of Tulsi (Ocimum sanctum) Leaf and Ginger (Zingiberofficinale) Powder as Feed Additives on Broiler Performance - Shende, Kavita A.; Dhuria, Rajesh K.; Goklaney, Deepika; Barolia, Yogesh K. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The study was conducted to evaluate the effect of tulsi leaf and ginger powder as feed additives on broiler performance. A total of 210, day-old chicks were divided into 7 groups in a completely randomized design, with 30 chicks in each group and reared for 42 days. Control group was provided with basal feed. T1 and T2 groups were supplemented with 0.5 and 1% of tulsi leaf powder, while G1 and G2 groups were supplemented with 0.5 and 1% of ginger powder in the ration, respectively. T1G1 group was supplemented with tulsi leaf and ginger powder each @ 0.25% of ration and T2G2 group was supplemented with tulsi leaf and ginger powder each @ 0.5% of ration. During starter and finisher period of trial, in T2G2 group, i.e., broilers fed with tulsi leaf and ginger powder at 0.5% each had significantly higher (p <0.01) body weight gain and improved (p <0.01) feed conversion ratio as compared to control and rest of the groups. Significantly lowest feed intake (p <0.01) during the starter period was observed in T2G2 group, and in G1 group during the finisher period of trial. It could be concluded that tulsi leaf and ginger powder @ 0.5% each can be supplemented to improve growth performance and FCR of broilers.